The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00066-008-1817-3
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral Cavernous Hemangioma after Cranial Irradiation in Childhood

Abstract: These findings and previously published cases show that cavernous hemangiomas may occur after irradiation of the brain several years after the end of therapy irrespective of the radiation dose and type of malignancy. Particularly children < 10 years of age at the time of irradiation are at higher risk. Since patients with RICH frequently do not show symptoms but hemorrhage is a possible severe complication, imaging of the central nervous system should be performed routinely for longer follow- ups, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 30 publications
2
62
2
6
Order By: Relevance
“…16,20 Strenger and colleagues, who reported 8 RICMs in a series of 171 pediatric patients with cancer, found RICM to be more likely and have shorter latency if radiation therapy occurred in the first 10 years of life. 36 Taking together patients of all ages with RICM, our finding of a median latency of 12 years from radiation therapy to CM diagnosis is consistent with data from Keezer and Del Maestro, who gathered the majority of previously reported RICM cases (n = 84) and added 1 of their own in a 2009 report in which the mean and median latencies were 10.3 and 8 years, respectively. 20 In a stratified comparison of pediatric and adult RICM, we found that radiation treatment at a younger age makes multiple RICMs more likely.…”
Section: Discussionsupporting
confidence: 88%
“…16,20 Strenger and colleagues, who reported 8 RICMs in a series of 171 pediatric patients with cancer, found RICM to be more likely and have shorter latency if radiation therapy occurred in the first 10 years of life. 36 Taking together patients of all ages with RICM, our finding of a median latency of 12 years from radiation therapy to CM diagnosis is consistent with data from Keezer and Del Maestro, who gathered the majority of previously reported RICM cases (n = 84) and added 1 of their own in a 2009 report in which the mean and median latencies were 10.3 and 8 years, respectively. 20 In a stratified comparison of pediatric and adult RICM, we found that radiation treatment at a younger age makes multiple RICMs more likely.…”
Section: Discussionsupporting
confidence: 88%
“…The cumulative incidence increased up to 5% at 15 years after radiation exposure. In children less than 10 years old at the time of radiation, the cumulative incidence has been reported to be as high as 8.5% at 15 years, suggesting that age is truly a key risk factor for the development of RICH [3]. This is in sharp contrast to a prevalence of only 0.3–0.7% among the general population without any radiation exposure [5].…”
Section: Introductioncontrasting
confidence: 43%
“…The best time to operate varies from patient to patient according to the opinion of the treating team; however, the major criteria for intervention include a change in size, hemorrhage or symptom development. In a series of 8 patients previously reported who developed RICH, 3 underwent surgery, all secondary to an increase in size of the lesions [3]. The risk of spontaneous bleeding has been reported from 0.5 to 3% each year but it is most likely influenced by other factors such as location and ongoing morbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the existing retrospective analyses are limited in validity due to little information about actual organ dose levels and older radiation techniques that can not be compared to modern therapy approaches [4,12]. However, detailed data regarding dose-volume-effect relationships of radiotherapy for organs in children and adolescents are indispensable for exact planning of combined modalities in tumor therapy.…”
Section: Introductionmentioning
confidence: 99%